First Tarsometatarsal Joint Shape and Orientation: Can We Trust in Our Radiographic Findings?. Issue 3 (14th September 2018) - de Cesar Netto, Cesar; Staggers, Jackson; Smith, Walter; Lee, Sung; Phillips, Sierra; Pinto, Martim; Dos Santos, Alexandre Godoy; Roberts, Lauren; Sahranavard, Bahman; Shah, Ashish
Category: Bunion Introduction/Purpose: Studies have demonstrated that patients with hallux valgus (HV) deformities have increased mobility in the first tarsometatarsal (TMT) joint. Anatomical factors widely considered to play a role in the instability are shape and frontal plane orientation of the joint. An oblique rather than horizontal orientation of the articular surfaces and a round shape, rather than a flat shape, are believed to predispose to the deformity. The purpose of this study was to assess whether the shape and angulation of the first TMT joint are affected by the positioning of the foot and orientation of the x-ray beam. Methods: Ten adult above knee fresh frozen cadaveric specimens were used, with a mean age of 79.9 (range, 54-88) years. There were no clinical forefoot deformities noted in any of the feet. One of the specimens had moderate ankle arthritis and one had a mild cavus-varus. A radiolucent loading apparatus was built that, allowing neutral positioning of a plantigrade foot and controlled angulation of 5o, 10 o, 15o and 20o in dorsiflexion, plantarflexion, inversion and eversion. Fluoroscopic images were obtained of each cadaveric specimen in all seventeen different positions, with the x-ray beam perpendicular to the floor and aiming to the base of the 1st metatarsal. Two blinded orthopaedic surgeons independently measured the 1st tarsometatarsal (TMT) joint angle and graded the distal articular cartilage of the medial cuneiform as flat or curved. Readers also graded the image quality into assessing the joint into "Low", "Intermediate" and "Good". Results: 1st TMT joint angle was 112.92o ± 6.89o. Values were significantly different between cadaveric specimens (p<.0001). There was a tendency for increased valgus angulation of the joint in images positioned in neutral, plantarflexion and inversion and decreased valgus angulation with dorsiflexion and eversion.Regarding the shape of the distal articular cartilage of the medial cuneiform, joints with flat configuration showed significantly increased mean 1st TMT joint angle when compared to curved surfaces (115.9o vs. 110.7o, p<.0001). In 8 out of 10 of the cadaveric specimens (80%) the shape of the 1st TMT joint changed between curved or flat configuration depending on the positioning of the foot. In only 2/10 (20%) the joint configuration remained the same for all different positions (one flat and one curved). Conclusion: Our cadaveric study found that the shape and angulation of the first TMT joint is affected by the positioning of the foot and orientation of the x-ray beam. Clinical usefulness of the 1st TMT radiographic anatomical characteristics is limited and should not influence in the treatment of patients with possible instability the first tarsometatarsal (TMT) joint.